Control de los inventarios en la micro empresa de productos manabitas “el socito” de la ciudad de Babahoyo. - Chiriguayo Quinto, Jessica Mariella (2022)
The purpose of this research is to analyze the inventory control of the micro company Productos Manabitas "EL SOCITO" in order to execute the administration in the micro company and thus know what the deficiencies that exist within it are. In carrying out this work, the descriptive method has been used, which has allowed analyzing points focused on the control of the inventories of the micro-enterprise in order to detect the problems that arise within it, through the application of the tool such as the interview, which was made to the owner and administrator of "EL SOCITO" through a variety of questions focused on the control of the inventories of the micro-enterprise, from which information was obtained on the method used to control their products. . The result obtained from this work shows that there are drawbacks in the control of the inventories of the micro company Productos Manabitas "EL SOCITO" in which the owner does not have the knowledge to apply an adequate control of their products in the income and expenses for bring better performance and greater profitability in it.